Microplastics and cancer progression: A comparative study of 2D and 3D gastric cancer models using ISOCompliant protocols - Parisasadat Rafazi; Hamed Haghi-Aminjan; Zeinab Bagheri; Mahban Rahimifard (Results in Engineering)
Microplastics have emerged as a significant global environmental concern, yet the absence of standardized protocols for assessing their toxicity remains a challenge. To address this gap, we applied the ISO 10,993–5:2009 and ISO 10,993–12:2012 standards for the first time to evaluate the effects of microplastics on cancer progression. Our study utilized both two-dimensional and three-dimensional models of gastric cancer to investigate the potential role of microplastics in promoting cancer growth. The MTT assay results revealed that the highest concentrations of polyethylene microplastics (PE-MPs) and polypropylene microplastics (PP-MPs) enhanced the proliferation of gastric cancer cells at both 24 and 72 h. After 24 h, AGS cells treated with PE-MPs and PP-MPs exhibited increased viability, reaching 116.08 % ± 15.55 and 118.78 % ± 13.96, respectively; however, this increase was not statistically significant. In contrast, after 72 h, AGS cells showed significantly enhanced growth, with viability reaching 122.37 % ± 9.28 for PE-MPs and 131.51 % ± 3.05 for PP-MPs (p < 0.001). In the three-dimensional model, live/dead staining results after seven days indicated that spheroids exposed to microplastics demonstrated greater cell survival compared to the control group. The percentage area growth of spheroids was 7.93 % ± 1.5 for the control, 13.93 % ± 4.85 for PE-MPs, and 19.59 % ± 1.61 for PP-MPs, with the increase in PP-MPs being statistically significant (p < 0.05). Additionally, microplastics did not penetrate the three-dimensional gastric cancer within seven days. This research highlights the potential impact of microplastics on cancer development and introduces a novel methodological approach.